Constitutionality of alternative dispute resolution methods: Presentation presented within the framework of the Second Nicaraguan Congress of Alternative Dispute Resolution Methods - Rodríguez, Gerardo (Cuaderno Jurídico y Político, 2016)
The progressive use of methods of alternative conflict resolution is a priority need in the context of a democratic society. Promoting new ways of solving conflicts between individuals through the word, and reaching agreement and consensus ensure a sustained peace in Nicaraguan society, once polarized in armed conflicts. At the institutional level, the State is responsible for the promotion of these methods in order to invite society to be part of the construction of a climate of security and peace, being protagonist of the resolution of everyday problems. Then, taking into account its importance, it is necessary to investigate whether these methods have place in the principles and constitutional orders, so that their application becomes necessary and privileged in the state daily work